ARCHETYPE ANALYSIS OF THE MAIN CHARACTER IN WINSTON GROOM’S MOVIE FORREST GUMP - Syamsul Bahri; Safha Dwi Kayla; Ridwan Karo Sekali (Universitas 17 Agustus 1945 Surabaya, 2022)
The distinctive traits of the conduct of the main character in the Forrest Gump movie, such as being both foolish and quick to understand, diligent, cranky, selfish, and subservient, have piqued the researchers’ curiosity in delving deeper into his character or personality by utilizing an archetypal approach. This research can educate and assist people to understand human character or personality. The purpose of this study is to explore more about the kinds of archetypes found in the main character of Forrest Gump movie. The researchers applied a qualitative descriptive method in which the exact procedure involved in the research process was known as research design: data gathering, classy, identifying, and analyzing some monologues and dialogues in this movie contextually and theoretically. The research subject was the main character of Forrest Gump movie. The result showed that from fifteen samples of data, there were five types of archetypes such as persona, ego, shadow, self, and anima. The most common archetype of the main character in this movie is persona. It shows that Forrest portrayed a different personality in public than he is. Anima is the least archetype in this movie and it indicated that Forrest has a feminine image which his submissive nature.